PENERAPAN METODE WEIGHTED PRODUCT DALAM SISTEM PENENTUAN KARYAWAN TERBAIK - Wahyuni, Sri; Hastanto, Wandarah Puji (Jurnal informasi dan komputer, 2024)
Employee assessment at UD. Kurnia Department Store is still done manually using Microsoft Excel, which often causes inaccuracy and lack of transparency. This may make it more difficult to choose the finest workers. Therefore, this study applies the Weighted Product (WP) method to improve objectivity and efficiency in employee assessment. The WP method normalizes the weight of each criterion such as attendance, cooperation, work quantity, and responsibility to determine employee rankings. The implementation of this system results in more accurate, faster, and consistent assessments. This system is designed to assist management in making better decisions regarding the selection of the best employees each year.